Job crafting and well-being at work: an exploratory analysis during health emergency period - Signore , Fulvio; Cortese, Claudio Giovanni; Parisi, Sara; Russo, Vincenzo; Zito, Margherita; Ingusci, Emanuela (La Medicina del Lavoro, 2020)
Introduction: During the health emergency in 2020, in order not to interrupt production processes and at the same time to protect the health of citizens and workers, alternative working methods were adopted different from the traditional ones, to which workers were directed without any previous notice or specific training. Aims: The purpose of the research is to explore the relationships between meaning of work, job crafting and emotional exhaustion during the first month of lockdown in the Italian territory. The study therefore aims to identify possible strengthening factors related to working well-being. Methods: The different constructs were detected through an online questionnaire from 11 March to 2 April 2020, involving 405 subjects. After verifying the reliability of the constructs, a mediation model was performed using nonparametric structural equations (PLS-SEM). Results: Model’s constructs show adequate reliabilities. The study highlights the total mediation of job crafting in the relationship between the meaning of work and emotional exhaustion. In particular, the regression relationship between meaning of work and emotional exhaustion is equal to c’=-0.04, p=0.480. On the contrary, the relationship between the meaning of work and job crafting is a=0.44 (p<0.001), and the one between job crafting and emotional exhaustion is b=-0.14, p=0.014. Conclusions: The results suggest that job crafting can be considered a factor able to buffer workers’ emotional exhaustion and can guide new lines of intervention, in particular in relation to post-emergency reactivation.